Human olfactory communication: current challenges and future prospects - Roberts, S Craig; Havlíček, Jan; Schaal, Benoist (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2020)
Although anthropologists frequently report the centrality of odours in the daily lives and cultural beliefs of many small-scale communities, Western scholars have historically considered the sense of smell as minimally involved in human communication. Here, we suggest that the origin and persistence of this latter view might be a consequence of the fact that most research is conducted on participants from Western societies who, collectively, were rather old (adults), deodorized and desensitized (ODD) to various aspects of olfactory perception. The view is rapidly changing, however, and this themed issue provides a timely overview of the current state-of-the-art on human chemocommunication. Based on evolutionary models of communication, the papers cover both general mechanisms of odour production by 'senders' and odour perception by 'receivers'. Focus on specific functional contexts includes reciprocal impact of odours between infants and mothers, the role of odour in mate choice and how odours communicate emotion and disease. Finally, a position paper outlines pitfalls and opportunities for the future, against the context of the replication crisis in psychology. We believe a more nuanced view of human chemical communication is within our grasp if we can continue to develop inter-disciplinary insights and expand research activities beyond ODD people. This article is part of the Theo Murphy meeting issue 'Olfactory communication in humans'.
Keywords: WEIRD; odoranty; čichová percepce; Nonverbal Communication; Odorants; semiochemistry; Humans; perception; neverbální komunikace; lidé; smell; chemical communication; pheromone; Olfactory Perception